Pengaruh Reward, Punishment, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Bank Muamalat Di Kota Bengkulu - Putri Lestari, Nadia; Markoni Markoni; Fauzan Fauzan (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This research aims to determine the magnitude of the influence of rewards on employee performance at Bank Muamalat in Bengkulu City, to determine the magnitude of the influence of punishment on employee performance at Bank Muamalat in Bengkulu City, to determine the magnitude of the influence of the work environment on employee performance at Bank Muamalat in Bengkulu City, to determine the magnitude of the influence of reward, punishment, and the work environment on employee performance at Bank Muamalat in Bengkulu City. This research method is exploratory. With a total sample of 60 respondents, data collection was carried out by distributing questionnaires. Based on the research results, it was found that there was an influence of reward (X1) on employee performance (Y). Bank Muamalat Ho was rejected and Ha was accepted. It was found that variable X1 had an effect on employee performance (Y). There is an influence of punishment (X2) on employee performance (Y) of Bank Muamalat. There is an influence of the work environment (X3) on employee performance (Y) of Bank Muamalat. From the significance value obtained, variable X3 has an effect on employee performance (Y). And it can be concluded that together the independent variables have an effect on the dependent variable